The Revivalism of Veiled Female Students: An Account of Their Views of Democracy in Indonesia - Iswahyudi Iswahyudi; Udin Safala; Umi Kulsum (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2019)
The issue of veiled female students has become a polemic, especially among the State Islamic Religious Colleges (PTKIN) in Indonesia. This is because female students wearing veils obstructs the learning activities and is also viewed as a sign of Islamic revivalism. Although this revivalism is considered as a barrier to the Islamic moderatism promulgated by the state and PTKIN, excessive concern about it is not always true. Azyumardi Azra once argued that revivalism does not always lead to radicalism and destruction and also referred to it as “inward-oriented” revivalism, which is a form of personal religiosity while practicing and living according to Islam. This article attempts to examine the revivalism of veiled female students based on their views of democracy in Indonesia. By employing the phenomenological approach, this study discovered that these students hold positive views of democracy as a means of societal welfare creation in Indonesia. However, they asserted that this democracy should be rejuvenated as it is not only a concept but also a practical matter, which must be present in the realities of the Indonesian people. Consequently, this view demonstrates inward-oriented revivalism, not a radical and destructive one.